Monosubstituted thermotropic ferrocenomesogens: an overview 1976-1999 - Imrie, Christopher; Engelbrecht, Pieter; Loubser, Christa; McCleland, Cedric W. (Applied organometallic chemistry, 2001)
Research in the late 1940s in academic institutions, most notably the University of Hull in the UK, led to the development of liquid crystal display technology in the 1970s, which has subsequently had a large impact throughout the world. The liquid crystal technology is based on simple organic molecules. Since the late 1980s, some liquid crystal scientists have turned their attention to investigating the effect of introducing a metal atom into the systems. This review focuses on the major developments in the field of ferrocenyl‐containing liquid crystals in which the organometallic group is situated in a terminal position with respect to the core of the molecule. Metallomesogens with terminal metal atoms are not very common, since it can be deduced from the theory of organic liquid crystals that bulky terminal groups would not be conducive to the stabilization of liquid crystal phases. Nevertheless, a terminal ferrocenyl group can stabilize a nematic liquid crystal phase and examples of this will be discussed in this review. Copyright © 2001 John Wiley & Sons Ltd.